Understanding the role of eIF4A in gene regulation in health and disease - Webb, Thomas E. (2012)
Eukaryotic initiation factor 4A (eIF4A) is an ATP-dependent RNA helicase responsible for unwinding the secondary structure of mRNAs. In humans, eIF4A exists as three separate paralogs: eIF4AI and eIF4AII possess a high degree of homology while eIF4AIII is distinct. Knockdown of eIF4AII had no effect on the expression of a reporter construct containing a structured RNA hairpin. Knockdown of eIF4AI and treatment with hippuristanol (an eIF4A inhibitor) caused a dramatic reduction in the hairpin-mediated gene. This reporter system was developed as part of this project to act as a screen for eIF4A activity along with an in vitro screening approach.